1999
DOI: 10.1093/tropej/45.3.161
|View full text |Cite
|
Sign up to set email alerts
|

Does treatment change the outcome of seizures and computerized tomographic lesions in intracranial granulomas?

Abstract: In children, intracranial granuloma diagnosed on computerized tomography (CT) scan and presenting with seizures as the sole manifestation has traditionally been treated with antitubercular (ATB) therapy or albendazole (Alb) in addition to antiepileptic drugs (AED). This study was conducted to determine whether AED therapy alone or specific treatment (ATB + Alb) influences the outcome of seizures and the CT lesion. Sixty-eight children presenting with seizures along with intracranial granuloma on CT scan were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
3
1
Order By: Relevance
“…Probably these calcified foci or perilesional gliosis acted as the trigger for recurrence of seizures. This significant improvement in EEG is not in accordance with some previous studies [14,15] and probably may be due to the high incidence of active and transitional lesions which responded favorably to therapy.…”
Section: Discussioncontrasting
confidence: 91%
See 1 more Smart Citation
“…Probably these calcified foci or perilesional gliosis acted as the trigger for recurrence of seizures. This significant improvement in EEG is not in accordance with some previous studies [14,15] and probably may be due to the high incidence of active and transitional lesions which responded favorably to therapy.…”
Section: Discussioncontrasting
confidence: 91%
“…Persistent headache, vomiting and focal neurologic deficit were probably due to residual cysts acting as space occupying lesions, whereas persistent calcified lesions were responsible for seizures. Opinions also vary on the use of anticonvulsants for control of seizures and the probability of seizure-free period after discontinuation of these drugs [13][14][15]. In the present study, carbamazepine was used for 6 months in all barring those showing toxicity, in whom phenytoin was added.…”
Section: Discussionmentioning
confidence: 92%
“…Similarly, in an unpublished study of a prospectively evaluated rural Honduran population with neurocysticercosis and epilepsy, Medina et al found that 76% had only calcifications, 9% cystic lesions, and 15% mixed lesions. There are at least three pieces of evidence that suggest calcified lesions play a role in epileptogenesis: 1) high prevalences of typical cerebral calcifications in patients with seizures or epilepsy in the absence of other etiologies,21,22 2) a positive correlation between endemic populations with increased proportions of calcification and seizure activity, and 3) an increased risk of continued seizure activity due to single cysticercal granuloma that calcify 23,24…”
Section: Association Of Calcifications With Seizuresmentioning
confidence: 99%
“…Strong evidence supports the role of calcified lesions in seizures; there is a high prevalence of cerebral calcifications in patients with seizures in the absence of other etiologies, and there is a positive correlation between endemic populations with increased proportions of calcification and seizure activity. In addition, individuals with calcified granulomas have increased risk of ongoing seizure [1417]. …”
Section: Clinical Manifestations Of Neurocysticercosis (Ncc)mentioning
confidence: 99%